Solvent-controlled direct radical oxyphosphorylation of styrenes mediated by Manganese(III). Issue 22 (2nd June 2016) - Zhang, Guo-Yu; Li, Cheng-Kun; Li, Da-Peng; Zeng, Run-Sheng; Shoberu, Adedamola; Zou, Jian-Ping
Abstract: Direct radical oxyphosphorylation of styrenes with diarylphosphine oxides and dialkyl phosphites mediated by Mn(OAc)3 is described. The solvent played a key role in this selective difunctionalization reaction. Graphical abstract: